Application of silase waste fruit leather technology in Suka village, Kecamatan Tigapanah, Karo District - Patriani, Peni; Ginting, Nurzainah; Hasanah, Uswatun; Mirwandhono, R. Edhy (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2019)
Karo Regency is one of the biggest coffee producing regions in North Sumatra Province. Plantation waste by-product from coffee production is the coffee seed waste which is usually discarded and causes environmental pollution. The purpose of this community service is to apply the waste of coffee fruit skin into sheep and goat feed using silage technology so that it can reduce the cost of feed for farmers. The method used is interviews and finding solutions to problems, training accompanied by practice using teaching media such as guidebooks, leaflets and banners, assistance and reinforcement supported by equipment from the service team so farmers are more interested. Outcomes of community service programs are improving farmers 'knowledge and skills, reducing the cost of animal feed using abundant coffee seed waste, reducing environmental pollution, developing the concept of business integration between plantations and animal husbandry so as to increase farmers' incomes. The results obtained are based on a long-term indicator that the utilization of coffee fruit seed waste using silage technology for animal feed can reduce feed costs, increase livestock production, increase farmers' skills and knowledge and can overcome waste pollution. It was concluded that silage technology using coffee seed waste is very effective to improve science, environmental health, income and farmers' standard of living.